Peningkatan Kemampuan Membaca Menggunakan Textured Lettering Card (Kartu Huruf Braille) Pada Murid Tunanetra Kelas VIII di SLB Al Qasmi Watampone - Winda Winda; Syamsuddin Syamsuddin; Purwaka Hadi (JURNAL ORTO DIDAKTIKA, 2023)
The problem in this research is the lack of reading ability in class VIII blind students at SLB Al Qasmi Watampone. The formulation of the problems in this study were 1) How was the ability to read braille in class VIII blind students at SLB Al Qasmi Watampone before using textured lettering cards (braille cards)? 2) How is the ability to read braille in class VIII blind students at SLB Al Qasmi Watampone after using textured lettering cards (braille cards)? 3) How is the ability to read braille in grade VIII blind students at SLB Al Qasmi Watampone through the use of textured lettering cards (braille cards)? This research is a qualitative research and a descriptive research type, which is to describe the increase in reading skills before and after the application of textured lettering cards (Braille card) to blind students in class VIII at SLB Al Qasmi Watampone. The data collection technique used is the action test technique. The subject of this study was a class VIII blind student. Descriptive analysis technique. The results of the study showed 1) The reading ability of blind students before using textured lettering cards (braille cards) was in the very poor category, 2) The reading abilities of blind students after using textured lettering cards (braille cards) were in the good category, 3) There improvement in reading skills of blind students after applying textured lettering cards (braille cards)..